Efektivitas lembar balik dan leaflet terhadap pengetahuan ibu hamil tentang pemberian makanan pendamping ASI (MP-ASI) - Rizka Masthura; Cut Yuniwati; Nurlaili Ramli (Jurnal SAGO Gizi dan Kesehatan, 2019)
Background: Breast milk contains all the nutrients a baby needs in the first six months after birth. Provision of MP-ASI before children aged six months is not recommended, because it can increase the likelihood of contamination and increase the risk of disease, especially diarrhea. Many factors are related to early breastfeeding. These factors include knowledge. Based on data obtained from the Baiturrahman Health Center in 2018, the total coverage of k4 was 871 with 909 infants and those who received exclusive breastfeeding were 191 (42.54%) and the rest were given complementary feeding.Objectives: To determine the effectiveness of flipcharts and leaflets on the knowledge of pregnant women about complementary feeding in the work area of the Baiturrahman Health Center in Banda Aceh City in 2019.Methods: : this study uses a quasy-experimental design, the research design used is the pre and post test two gruop design. The population in this study were all pregnant women in the Baiturrahman Community Health Center in Banda Aceh City, with a purposive sampling technique of 15 people. Analysis of the data in this study used the T-Paired test.Results: The results showed that the effect of flipcharts was more effective on increasing maternal knowledge about complementary foods after counseling (p = 0.002), compared to the effect of using leaflets (p = 0.016) on increasing maternal knowledge about complementary foods after counselingConclusions and Recommendations: It is hoped that this research can be a reference for researchers in conducting this research and can provide information about complementary feeding, so as to reduce the number of early supplementary feeding and increase the rate of exclusive breastfeeding.